AB0395 Depression as a Risk Factor for Joints Destruction in Rheumatoid Arthritis Patients. (9th June 2015) - Lisitsyna, T.A.; Veltishchev, D.; Gerasimov, A.; Seravina, O.; Kovalevskaya, O.; Zeltyn, A.; Novikova, D.; Novikov, A.; Alexandrova, E.; Smirnov, A.; Krasnov, V.; Nasonov, E.
Abstract : Background: Chronic depression is the most frequent psychiatric disorder in rheumatoid arthritis (RA) patients. It's considered that both depressive disorders and RA are stress-related and have a common proinflammatory pathogenesis. Moreover, depression decreases adherence to treatment and worsen the RA prognosis. That is why untreated depression may deteriorate the joints destruction in RA patients. Objectives: To determine the factors associated with joints destruction in RA patients by linear regression analysis and the influence of chronic depression on joints destruction. Methods: 125 RA patients were enrolled in this study. 86% were women with a mean age of 47.4±11.3 (M±m). The disease activity was assessed by DAS28 score. 52% of RA patients had a high activity of disease (DAS28>5, 1). 67% of patients were taking prednisone in mean dose 5±2.7 mg/day (M±m). 80% were taking DMARDs: most of them - methotrexate (45%) and leflunomide (21%). All patients were taking NSADs. Psychiatric disorders was diagnosed by psychiatrist in accordance with the ICD-10 criteria in semi-structured interview. Psychiatric scales were used: Hospital Anxiety and Depression Scale, Hamilton Anxiety Rating Scale. Anxiety-depressive disorders were diagnosed in 93, 6% of RA patients. Chronic depression - dysthymia and recurrent depressive disorder prevailed (32, 8% and 25, 6% accordingly). All patients were consulted by cardiologist. Dual-energy X-ray absorptiometry was used for osteoporosis detection. Results: Most of RA patients (65, 6%) had severe joints destruction - numerous bones erosions (III-IV X-ray stage of RA) or aseptic bones necrosis. The factors associated with severe joints destruction were found in Pearson correlation analysis. Then linear regression analysis was done and obtaining prognostic model showed that joints destruction was associated with RA (β=0, 520) duration, chronic depression (dysthymia and recurrent depressive disorder) (β=0, 235) and it's duration (β=-0, 124), osteoporosis (β=0, 196) and ischemic heart disease (β=0, 181), low body mass index (β=-0, 108) and high RF-IgM level (β=0, 121) (area under the ROC curve =0, 930). Conclusions: Chronic depression and it's duration along with RA duration, osteoporosis and ischemic heart disease, low body mass index and high rheumatoid factor level are the leading factors of joints destruction in RA patients. Disclosure of Interest: None declared